Income effects and trade agreements - David R. DeRemer (Hungarian Academy of Sciences, Institute of Economics, 2016)
This paper considers trade agreements in a sufficiently general framework to encompass both imperfectly competitive market structures and income effects in government objectives. We show that governments choose globally efficient policies if they act as if they do not value the impact of their policies on their terms of trade. The results confirm that additional international externalities that arise in imperfectly competitive settings are the result of government failure to equate markups between sectors with domestic policies, not demandside factors.
Keywords: F12; F13; F15; 330; trade agreements; income effects; non-homothetic preferences